2015
DOI: 10.1002/hup.2497
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of a dysregulation of the endogenous opioid system in antisocial personality disorder

Abstract: Around half the inmates in prison institutions have antisocial personality disorder (ASPD). A recent theory has proposed that a dysfunction of the endogenous opioid system (EOS) underlies the neurobiology of borderline personality disorder (BPD). In the present theoretical paper, based on a comprehensive database and hand search of the relevant literature, this hypothesis is extended to ASPD, which may be the predominant expression of EOS dysfunction in men, while the same pathology underlies BPD in women. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 289 publications
(263 reference statements)
3
15
0
Order By: Relevance
“…Proteomic analysis showed that the largest effect sizes were observed for opioid-binding protein/celladhesion molecule (OPCML), with the highest expression found in ASPD violent offenders, supporting the OPRD1 transcription data. These results support previous research which suggested that a deficient endogenous opioid system contributes to ASPD (Bandelow and Wedekind 2015).…”
Section: Personality Disorderssupporting
confidence: 92%
“…Proteomic analysis showed that the largest effect sizes were observed for opioid-binding protein/celladhesion molecule (OPCML), with the highest expression found in ASPD violent offenders, supporting the OPRD1 transcription data. These results support previous research which suggested that a deficient endogenous opioid system contributes to ASPD (Bandelow and Wedekind 2015).…”
Section: Personality Disorderssupporting
confidence: 92%
“…In fact, in a PET study, female borderline patients showed higher MOR concentrations at baseline relative to healthy controls, and a sustained sadness state was shown to activate the opioid system more potently in patients (Prossin et al ). Antisocial personality disorder has also been related to opioid system dysfunction in men, symmetrically to what has been reported in borderline females (Bandelow and Wedekind ). Patients with self‐injurious behaviors (a form of self‐aggression that tends to co‐occur with, and may possibly be related to suicidal behaviors) typically report that these behaviors help them decrease their emotional pain, an effect that might be due to the recruitment of endogenous opioid signaling (Kirtley et al ; Sher and Stanley ; Stanley et al ).…”
Section: Opioid Receptors and Social Behaviors During Adulthood: Pathsupporting
confidence: 60%
“…Our results showing a decrease in the expression of opioid delta receptor gene are in line with these previous findings. A recent theory suggests that a deficient endogenous opioid system contributes to antisocial personality, proposing that antisocial individuals attempt to stimulate their dysfunctional opioid system by the rewarding effect of substance abuse, and impulsive, sensationseeking, aggressive, and promiscuous behavior [11]. Our data suggest that dysfunction of the opioid system contributes to the phenotype of psychopathy, supporting the recently presented idea that partial opioid receptor agonists, such as (+)-naloxone might be the first effective treatment for psychopathy [11].…”
Section: Discussionmentioning
confidence: 99%
“…The gene linked to adult antisocial behavior, ABCB1, is also highly expressed in the brain, and implicated in substance abuse [9]. No underlying molecular pathways of severe antisocial and criminal behavior are known, but there is preliminary evidence on dysregulation of the endogenous opioid system and brain opioid receptors [11][12][13] in antisocial individuals. Also abnormal glucose metabolism leading to hypoglycemia has been observed as the strongest predictor for violent crimes [14].…”
Section: Introductionmentioning
confidence: 99%